Public Policy for Venture Capital A Comparison of the United States and Germany - Plagge, Arnd.; SpringerLink (Online service) (Wiesbaden : DUV, 2006)
Venture capital is widely regarded as an important driver of economic growth. While the USA has the largest and most sophisticated venture capital market in the world, its German counterpart has only recently begun to mature, and numerous governmental schemes exist that are meant to help speed up the development of the German market. Yet, little is known about the efficiency and the impact of these efforts. Arnd Plagge evaluates public policy for venture capital in the USA and Germany and presents a comprehensive study of the American and the German market for venture capital. Based on an extensive review of theoretical and empirical evidence, he shows that current German public policies aimed at fostering venture capital activity are severely flawed and that only a reversal of priorities, away from supply-side policies and towards a demand-oriented stance, will yield real payoffs.
The nature and role of venture capital -- Theoretical perspectives on public policy for venture capital -- Venture capital in the U.S. -- Venture capital in Germany -- Venture capital in the U.S. and Germany in comparison -- IPOs and venture capital -- Supply and demand in perspective -- Nothing ventured?.
Keywords: Finance; Economics; Management science; Finance; Finance, general; Economics, general; Electronic books